Biosci. J. 2017
DOI: 10.14393/bj-v33n1a2017-34021
|View full text |Cite
|
Sign up to set email alerts
|

Biomass flow and defoliation pattern in alexandergrass fertilized with nitrogen

Abstract: ABSTRACT:The determination of biomass flows can assist on improving pasture fertilization techniques, contributing to identify the best management methods and, in relation the use of fertilizers. Nitrogen deficiency in pastures can reduce forage production. On the other hand, there is an environmental concern on nitrogen (N) losses when this nutrient is used in excess and this concern guides the search for new grazing systems that optimize its use. Leaf biomass flow, intensity and frequency of defoliation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…The absence of N levels effect on leaf and stem expansion rates is not the usually reported answer when studies involve these two factors. These responses showed that, generally, as the nitrogen fertilization increase, a higher expansion rate of these components is observed (HUNDERTMARCK et al, 2017;TIECHER et al, 2017). Observations showed; however, a similar rate of leaves and stems expansion in the absence or presence of N fertilization.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The absence of N levels effect on leaf and stem expansion rates is not the usually reported answer when studies involve these two factors. These responses showed that, generally, as the nitrogen fertilization increase, a higher expansion rate of these components is observed (HUNDERTMARCK et al, 2017;TIECHER et al, 2017). Observations showed; however, a similar rate of leaves and stems expansion in the absence or presence of N fertilization.…”
Section: Discussionmentioning
confidence: 82%
“…The leaf expansion rate reduction of 0.000028 cm degree-days -1 per accumulated degreeday can be explained by Alexandergrass being a tropical climate species, which response to the temperature lowering and reduced daily light is the reduced leaf expansion (HUNDERTMARCK et al, 2017). Also, the approximation of the reproductive stage of Alexandergrass may have provided a greater nutrients allocation to the reproductive organs, in detriment of the leaf blades production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic unit of a forage plant is the tiller (HODGSON, 1990) which originate from the buds, which originates from the shoots, which are correlated with the rate of leaf appearance, are also influenced by interaction of various factors, such as light, temperature and nutrients in the soil, nitrogen availability can directly alter the tillering potential and have a direct link with leaf production (HUNDERTMARCK et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A produção e o acúmulo de forragem são determinados pelo processo dinâmico do surgimento, sobrevivência e morte dos perfilhos (Giacomini et al, 2009;Sousa et al ., 2019). O perfilhamento pode ser afetado por diversos fatores como temperatura, luz, água, estádio de desenvolvimento, macro e micronutrientes no solo, principalmente o nitrogênio (Langer, 1979;Hundertmarck et al, 2017). Compreender a dinâmica do perfilhamento torna-se essencial para definir práticas de manejo que garantam a produtividade, sustentabilidade e longevidade da pastagem ao longo do período produtivo (Sousa et al, 2019).…”
Section: Abstract Defoliation Frequency and Nitrogen Supply As Determinants Of Tillering And Forage Accumulation Of Brs Zuri Guineagrass unclassified